Barriers Factor Analysis of Fish Consumption Behavior in the Special Region of Yogyakarta and Central Java - Tony Wijaya; Farlianto Farlianto; Rullyana Puspitaningrum Mamengko (Agriekonomika, 2022)
The low level of fish consumption is the initial phenomenon of this study. This study's general objective is to determine the grouping of factors inhibiting fish consumption and confirm the suitability of the factors. This type of research is a survey. Samples were taken by fulfilling the criteria of purchasing marine fish for family consumption, food processing, or cooking for daily family consumption. The selection of research sites with consideration of areas with fish low consumption levels in DIY and Centre of Java. This study involved 427 respondents from various regions in DIY-Centre of Java. Data analysis techniques in this study used factor analysis and Anova. Based on data analysis, it is known that there are six factors of barriers to fish consumption, namely family member preferences, processing methods, distribution and availability, myths and knowledge, cost or price, and tastes. The factors are then successfully reduced to three main factors, namely individual, food, and environment characteristics.